Fabrication of functionally graded hydroxyapatite and structurally graded porous hydroxyapatite by using multi-walled carbon nanotubes. (December 2020) - Cho, Seungchan; Kim, Junghwan; Lee, Sang-Bok; Choi, Moonhee; Kim, Dong-Hyun; Jo, Ilguk; Kwon, Hansang; Kim, Yangdo
Abstract: Functionally graded MWCNT-HA composites were fabricated via hetero-aggregation and spark plasma sintering (SPS) process. The functionally-graded MWCNT–HA composites were further pressurelessly sintered at 1373 K in air condition to decompose the MWCNTs in the HA matrix. Consequently, structurally graded porous hydroxyapatite (HA) was successfully fabricated by introducing, followed by decomposing, of gradiently-included multi–walled carbon nanotubes (MWCNTs) at volume of 0–5 vol.%. Microstructure and Raman spectra of the sample clearly showed that no MWCNTs were present in the HA matrix. Moreover, pore and grain size of the structurally graded porous HA decreased with increasing MWCNT contents. It is expected that percolated MWCNTs make a degassing path for CO2 gas generated by MWCNT decomposition, and also prohibit grain growth of HA. The results indicate that these advanced, layered, structure-controlled functionally graded MWCNT–HA composites and structurally graded porous HA are promising for a variety of new and challenging structural and biomaterial applications.